Impact of acute coronary syndromes on survival of dialysis patients following surgical or percutaneous coronary revascularization in the United States. Issue 3 (June 2016) - Shroff, Gautam R; Solid, Craig A; Herzog, Charles A
Aims: We sought to evaluate survival of dialysis (chronic kidney disease (CKD) stage 5D) patients undergoing coronary revascularization procedures in the context of acute coronary syndrome (ACS) compared with absence of ACS. Methods and results: CKD 5D patients undergoing coronary revascularization, 2004–2009 ( n = 23, 033), were identified from the United States Renal Data System. Long-term survival was estimated by the Kaplan–Meier method and independent predictors of mortality using a comorbidity-adjusted Cox proportional hazards model. Among ACS patients ( n = 12, 473; 54%), revascularization procedures were coronary artery bypass grafting (CABG, n = 2910), drug-eluting stents (DESs, n = 6566), and bare metal stents (BMSs, n = 2997). All-cause survival rates following these procedures, respectively, were: in-hospital 90%, 96%, 93%; one-year: 66%, 67%, 58%; two-year: 53%, 48%, 43%. Among non-ACS patients ( n = 10, 560; 46%), procedures were CABG ( n = 3268), DESs ( n = 5278), and BMSs ( n = 2014). Survival rates following these procedures, respectively, were: in-hospital 94%, 99%, 98%; one year: 73%, 77%, 70%; two year: 61%, 59%, 55%. DESs (versus CABG) independently predicted mortality among ACS (hazard ratio 1.08; 95% confidence interval 1.02–1.15) but not non-ACS patients (1.01, 0.95–1.07); BMSs (versus CABG) independently predicted mortality among ACS (1.30, 1.21–1.38) and non-ACS (1.13, 1.05–1.22) patients. Conclusions: Among CKD 5D patients, survival was lower for ACS versus non-ACS indications following all revascularization strategies. CABG (versus DESs) was associated with higher long-term survival in the context of ACS; in the absence of ACS, long-term survival was similar after CABG or DESs. BMSs were consistently associated with worse outcomes.